The Advantages and Applications of Augmented Reality in Science Education - Anggi Datiatur Rahmat; Heru Kuswanto; Insih Wilujeng (Nusantara Science and Technology Proceedings, 2022)
Educational technologies can help students learn more interest and help the student to understand abstract concepts in science to become concrete with visuals in the learning process. The new technology in education is Augmented Reality (AR), which also has an excellent potential to make the learning process more enjoyable, coloring and helping students understand abstract concepts. The use of AR in science education has recently caught the attention of researchers and allowed students to gain real-world experience. Therefore, this study’s concept is the paper review about AR research in science education. The review discusses the application in the science subjects, including Physics, Chemistry, and Biology. Also, this paper explains the advantages of AR technology in science education. The review also shows that AR in science education has great potential and benefits for adapting to science education and highlights AR's limitations for future research.